G84(P) Clinical prediction rules to aid the recognition of abusive head trauma: A systematic review. (24th May 2017) - Pfeiffer, H; Crowe, L; Kemp, AM; Cowley, LE; Smith, A; Babl, FE
Abstract : Aims: Misdiagnosis of abusive head trauma (AHT) in the clinical setting can have serious consequences for the affected children and families. Clinical prediction rules (CPRs) can assist clinicians in deciding which children might have sustained injury as a result of AHT and should receive further investigation. The objective of this study was to compare CPRs in terms of derivation, population, definition of AHT and performance. Methods: We conducted a systematic review searching MEDLINE, Embase, PubMed and the Cochrane databases and included validated clinical prediction rules that focused on the detection of AHT in the clinical setting. Results: Our search returned 128 articles and we identified three recently published validated clinical prediction rules that met the inclusion criteria: the Paediatric Brain Injury Research Network (PediBIRN) 4-Variable AHT CPR, the Predicting Abusive Heat Trauma (PredAHT) tool and the Pittsburgh Infant Brain Injury Score (PIBIS) for AHT. The CPRs used different inclusion criteria and were designed for different populations and purposes: Head injury and intensive care unit admission (PediBIRN), intracranial injury and hospital admission (PredAHT) and well-appearing children in the emergency department with more than one suspicious symptom for AHT (PIBIS). The PediBIRN and PredAHT tools focused on children under 3 years of age, whereas the PIBIS tool only included children from 30–364 days of age. There was little overlap between the predictive variables used. Conclusion: The three CPRs that met our inclusion criteria differ in terms of population, stages of the diagnostic process and combinations of predictive variables used.